2011
DOI: 10.1002/smll.201100997
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Light through Magnetic Nanocavities

Abstract: The transmission of light through a metallic film stack on a transparent substrate, perforated with a periodic array of cylindrical holes/nanocavities, is studied. The structure is fabricated by using self-assembled nanosphere lithography. Since one layer in the film stack is made of a ferromagnetic metal (iron), exposure of the structure to a solution containing iron oxide nanoparticles causes nanoparticle accumulation inside the nanocavities. This changes the dielectric constant inside the nanocavities and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In order to illustrate this idea, we show in the Supporting Information that impressive figures of merit larger than 10 4 can be achieved with nanohole arrays with a triangular lattice, a type of lattice that can be realized with low-cost self-assembled nanosphere lithography. 38 In summary, we have put forward a new strategy for plasmonic sensing based on the use of hybrid magnetoplasmonic crystals and their MO properties. In particular, we have shown that the combination of the use of Au−Co−Au nanohole arrays with measurements of the transverse MO Kerr effect can lead to a tremendous enhancement of the figure of merit of this type of plasmonic sensors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to illustrate this idea, we show in the Supporting Information that impressive figures of merit larger than 10 4 can be achieved with nanohole arrays with a triangular lattice, a type of lattice that can be realized with low-cost self-assembled nanosphere lithography. 38 In summary, we have put forward a new strategy for plasmonic sensing based on the use of hybrid magnetoplasmonic crystals and their MO properties. In particular, we have shown that the combination of the use of Au−Co−Au nanohole arrays with measurements of the transverse MO Kerr effect can lead to a tremendous enhancement of the figure of merit of this type of plasmonic sensors.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In fact, nonmagnetic hybrid nanohole arrays of various kinds have already been investigated experimentally, 36,37 including hybrid Au−Fe−Au magnetoplasmonic crystals fabricated by using selfassembled nanosphere lithography. 38 Let us also mention that the fabrication and characterization of cm 2 disordered nanohole arrays based on Au−Co multilayers have been recently reported, 39 using a low-cost fabrication technique that also allows for periodically ordered systems.…”
mentioning
confidence: 99%
“…Transparent magnetic materials play an important role in bioanalytical applications, magneto-optical switches, magnetooptical sensors, modulators, optical circulators, and optical isolators. [1][2][3] Preparation of transparent magnetic materials with excellent magnetic, optical, mechanical, and thermal properties has attracted great interest over the last twenty years. [4][5][6][7] A transparent magnetic thin polyvinyl alcohol (PVA) lm is prepared by spin coating a solution of magnetite ne particles on glass substrates, and followed by drying at 80 C and solidifying at 200 C in a magnetic eld.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples prove that the widely tunable grating-coupled resonances, when using nanovoid and nanohole arrays, enable high sensitivity biosensing [19]. Combined spectral and near-field studies revealed that the transmittance minima (maxima) exhibit smaller (larger) sensitivity on hexagonal and square hole arrays [20][21][22]. Moreover, special individual scatterers such as hole doublets ensure enhanced sensitivity due to the antennas that appear at their apexes [4,23].…”
Section: Introductionmentioning
confidence: 98%